Quasilinear periodic boundary-value problem - Botyuk, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study a periodie boundary-value problem for the quasilinear equation u tt − u xx = F[u, u t , u x ]. We find conditions under which a theorem on the uniqueness of a solution is true.